The eukaryotic P loop NTPase Nbp35: An essential component of the cytosolic and nuclear iron–sulfur protein assembly machinery - Hausmann, Anja (National Academy of Sciences, 2005)
Soluble P loop NTPases represent a large protein family and are involved in diverse cellular functions. Here, we functionally characterized the first member of the Mrp/Nbp35 subbranch of this family, the essential Nbp35p of Saccharomyces cerevisiae. The protein resides in the cytosol and nucleus and carries an Fe/S cluster at its N terminus. Assembly of the Fe/S cluster requires the mitochondrial Fe/S cluster (ISC)-assembly and -export machineries. Depletion of Nbp35p strongly impairs the activity of the cytosolic Fe/S protein, isopropylmalate isomerase (Leu1p), whereas mitochondrial Fe/S enzymes are unaffected. Moreover, defects in the de novo maturation of various cytosolic and nuclear Fe/S proteins were observed in the absence of Nbp35p, demonstrating the functional involvement of Nbp35p in the biogenesis of extramitochondrial Fe/S proteins. Furthermore, Nbp35p genetically interacts with the closely similar P loop NTPase, Cfd1p, and the hydrogenase-like Nar1p, both of which were recently shown to perform a crucial function in cytosolic and nuclear Fe/S protein biogenesis. Hence, our study suggests that eukaryotic Nbp35 NTPases function in Fe/S protein maturation. The findings provide strong evidence for the existence of a highly conserved and essential machinery dedicated to assembling cytosolic and nuclear Fe/S proteins.